Late gadolinium enhancement confined to the right ventricular insertion points in hypertrophic cardiomyopathy: an intermediate stage phenotype?. (14th June 2015) - Bravo, Paco E.; Luo, Hong-Chang; Pozios, Iraklis; Zimmerman, Stefan L.; Corona-Villalobos, Celia Pamela; Sorensen, Lars; Kamel, Ihab R.; Bluemke, David A.; Wahl, Richard L.; Abraham, M. Roselle; Abraham, Theodore P.
Abstract: Aims: To investigate whether hypertrophic cardiomyopathy (HCM) patients with late gadolinium enhancement (LGE) confined to the right ventricular insertion points (RVIP) differ phenotypically from patients without LGE or intramural LGE in the left ventricle (LV). Methods and results: Sixty-two HCM patients underwent cardiac magnetic resonance for quantification of LGE (% LV mass) and were classified as group (i) no-LGE ( n = 18), group (ii) LGE-RVIP ( n = 19), and group (iii) intramural LGE ( n = 25). All patients also underwent vasodilator N-13 ammonia PET to quantify myocardial blood flow (MBF) and myocardial flow reserve (MFR), and echocardiography to measure longitudinal LV strain. LGE extent (17 ± 11% vs. 4 ± 4% vs. 0%; P < 0.001) and LV thickness (21.7 ± 3.4 vs. 18.8 ± 3.9 vs. 16.3 ± 2.8 mm; P < 0.001) were significantly greater in group 3, intermediate in group 2, and lower in group 1. In contrast, stress MBF (1.62 ± 0.44 vs. 1.90 ± 0.37 vs. 2.22 ± 0.48 mL/min/g; P < 0.001); MFR (1.92 ± 0.47 vs. 2.15 ± 0.52 vs. 2.71 ± 0.52; P < 0.001), and longitudinal LV strain (−11.4 ± 3.8 vs. −12.6 ± 3.2 vs. −14.4 ± 4.1%; P = 0.04) were lower in group 3, intermediate in group 2, and higher in group 1. Conclusions: From an imaging viewpoint, patients with LGE confined to only the RVIP appear to represent an intermediate-stage phenotype between patients with no LGE and intramural LGE in the LV.